TeenPower: an integrated architecture for an mHealth platform designed for e-Empowering teenagers to prevent obesity: A showcase of the TeenPower platform. - Sousa, Pedro Miguel Lopes de (2018)
Adolescents, reportedly, easily adopt a sedentary lifestyle and unhealthy behaviors. Furthermore, the use of smartphones, especially in this age group, is made on a daily basis. In this context, the TeenPower Project includes an mHealth platform integrated in an intervention programme to engage teenagers to embrace more healthier lifestyle behaviors. This paper describes the technical aspects of the development and implementation of the software applications that compose the TeenPower Platform. The platform consists of two applications: a mobile app (Android) to be used by adolescents, mainly for self-monitoring and educational purposes; and the backoffice (web) application to be used by teachers and health professionals. Both applications are integrated and work through a web service (REST-based) API, which allows them to exchange data seamlessly, keep all related contents updated and enhance communication between adolescents and health professionals.